The ‘White Stone’ mythologem in the poetics of Innokenty Annensky - Шелогурова, Галина (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2016)
The mythologem ‘white stone’ seems to be one of the most significant motifs in Innokenty Annensky’s poetics. In the article an attempt has been made to demonstrate a close connection between Annensky’s ‘white stone’ and the island of Leucas (Lefkada), – a famous mythological topos of Greek culture. The author proceeds from the ‘artistic semantics’ of this island (the cult od Apollo, Sapho’s legend) on the one hand, and from the concept of oblivion, strongly associated with this place (Homer, Odyssey, 24, 11), on the other.